Antioxidative effect of lipophilized caffeic acid in fish oil enriched mayonnaise and milk. (15th January 2015) - Alemán, Mercedes; Bou, Ricard; Guardiola, Francesc; Durand, Erwann; Villeneuve, Pierre; Jacobsen, Charlotte; Sørensen, Ann-Dorit Moltke
Highlights: Promising antioxidant effectiveness of lipophilized caffeic acid in oil-in water emulsions. Different " critical chain length " for the caffeates in different emulsion systems. Not predictable " critical chain length " of phenolipids in oil-in-water emulsions. First confirmation of cut-off effect theory in real food systems. Abstract: The antioxidative effect of lipophilized caffeic acid was assessed in two different fish oil enriched food products: mayonnaise and milk. In both emulsion systems, caffeic acid esterified with fatty alcohols of different chain lengths (C1–C20) were better antioxidants than the original phenolic compound. The optimal chain length with respect to protection against oxidation was, however, different for the two food systems. Fish oil enriched mayonnaise with caffeates of medium alkyl chain length (butyl, octyl and dodecyl) added resulted in a better oxidative stability than caffeates with shorter (methyl) or longer (octadecyl) alkyl chains. Whereas in fish oil enriched milk emulsions the most effective caffeates were those with shorter alkyl chains (methyl and butyl) rather than the ones with medium and long chains (octyl, dodecyl, hexadecyl and eicosyl). These results demonstrate that there might be an optimum alkyl chain length for each phenolipid in each type of emulsion systems.